2011
DOI: 10.1172/jci42040
|View full text |Cite
|
Sign up to set email alerts
|

Tie1 attenuation reduces murine atherosclerosis in a dose-dependent and shear stress–specific manner

Abstract: Although the response of endothelial cells to the disturbed blood flow in the vicinity of atherosclerotic lesions is known to be distinct from that elicited by nonatherogenic laminar flow, the mechanisms involved are poorly understood. Our initial studies confirmed that expression of the endothelial receptor tyrosine kinase Tie1 was evident at regions of atherogenic flow in mature animals. We therefore hypothesized that Tie1 plays a role in the endothelial response to atherogenic shear stress. Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…Microarray analysis of HUVEC gene expression under static and 2 Pa laminar shear stress showed CLEC14A and ROBO4 were markedly upregulated (significant false discovery rate of o12% and o1% respectively) in the absence of shear stress. Real-time PCR analysis confirmed the predicted downregulation of CLEC14A and ROBO4 expression (Figure 9a) in HUVEC exposed to 2 Pa of shear stress for 24 h. TIE1 is a validated marker of reduced shear stress at the endothelial surface (Chen-Konak et al, 2003;Porrat et al, 2004;Woo et al, 2011). Double immunofluorescence staining of TIE1 and CLEC14A showed that they co-localised on tumor vessels (Figure 9b).…”
Section: Clec14a and Vascular Development In Zebrafishsupporting
confidence: 54%
“…Microarray analysis of HUVEC gene expression under static and 2 Pa laminar shear stress showed CLEC14A and ROBO4 were markedly upregulated (significant false discovery rate of o12% and o1% respectively) in the absence of shear stress. Real-time PCR analysis confirmed the predicted downregulation of CLEC14A and ROBO4 expression (Figure 9a) in HUVEC exposed to 2 Pa of shear stress for 24 h. TIE1 is a validated marker of reduced shear stress at the endothelial surface (Chen-Konak et al, 2003;Porrat et al, 2004;Woo et al, 2011). Double immunofluorescence staining of TIE1 and CLEC14A showed that they co-localised on tumor vessels (Figure 9b).…”
Section: Clec14a and Vascular Development In Zebrafishsupporting
confidence: 54%
“…The overall healthy condition of the Tie1-deleted mice is consistent with the conclusion that their possible vascular changes would have to be relatively subtle. Furthermore, recent experiments have shown that atherosclerosis is inhibited by partial Tie1 deletion (20), which argues that decreased Tie1 function might be beneficial not only in cancer, but also in atherosclerosis patients. Thus, our present findings elucidate a previously unknown regulatory system for angiogenesis and propose Tie1 as a potential new target for anti-angiogenic therapy that potentially holds clinical relevance now, more than 20 years after its isolation (59), when we first suggestedbased on its enhanced expression pattern in the tumor vasculature (19) -the possible involvement for this interesting receptor in tumorigenesis and other angiogenesis-dependent diseases, such as diabetic retinopathy, atherosclerosis, and arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Tie1 expression is increased in adults during wound healing, ovarian follicle maturation, and tumor angiogenesis (11,19). According to Woo et al, postnatal loss of 40%-80% of Tie1 did not result in obvious pathology, but instead conferred an atheroprotective effect, in a murine model (20).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1 Now the team plans to study the mechanism underlying the therapeutic effect. The findings could represent a new indication for sanofi-aventis Group, which has licensed at least two therapies targeting tyrosine kinase receptor proteins in cancer and wound healing.…”
mentioning
confidence: 99%